Prevalence of rosacea in the general population of Germany and Russia - The RISE study - Tan, J.; Schöfer, H.; Araviiskaia, E.; Audibert, F.; Kerrouche, N.; Berg, M. (Journal of the European Academy of Dermatology and Venereology, 2016)
Background There is an unmet need for general population‐based epidemiological data on rosacea based on contemporary diagnostic criteria and validated population survey methodology. Objective To evaluate the prevalence of rosacea in the general population of Germany and Russia. Methods General population screening was conducted in 9–10 cities per country to ensure adequate geographic representation. In Part I of this two‐phase study, screening of a representative sample of the general population (every fifth person or every fifth door using a fixed‐step procedure on a random route sample) was expedited with use of a questionnaire and algorithm based on current diagnostic criteria for rosacea. Of the subjects that screened positive in the initial phase, a randomly selected sample (every third subject) t`hen underwent diagnostic confirmation by a dermatologist in Part II. Results A total of 3052 and 3013 subjects (aged 18–65 years) were screened in Germany and Russia respectively. Rosacea prevalence was 12.3% [95%CI, 10.2–14.4] in Germany and 5.0% [95%CI, 2.8–7.2] in Russia. The profile of subjects with rosacea (75% women; mean age of 40 years; mainly skin phototype II or III, majority of subjects with sensitive facial skin) and subtype distribution were similar. Overall, 18% of subjects diagnosed with rosacea were aged 18–30 years. Over 80% were not previously diagnosed. Within the previous year, 47.5% of subjects had received no rosacea care and 23.7% had received topical and/or systemic drugs. Over one‐third (35% Germany, 43% Russia) of rosacea subjects reported a moderate to severe adverse impact on quality of life. Conclusion Rosacea is highly prevalent in Germany (12.3%) and Russia (5.0%). The demographic profile of rosacea subjects was similar between countries and the majority were previously undiagnosed.